Phillips Curves, Phillips Lines and the Unemplyment Costs of Overheating - Laxton, Douglas (IMF Working Papers; Working Paper, 1997)
Most empirical work on the U.S. Phillips curve has had a strong tendency to impose global linearity on the data. The basic objective of this paper is to reconsider the issue of nonlinearity and to underscore its importance for policymaking. After briefly reviewing the history of the Phillips curve and the basis for convexity, we derive it explicitly using standard models of wage and price determination. We provide some empirical estimates of Phillips curves and Phillips lines for the United States and use some illustrative simulations to contrast the policy implications of the two models.